DISTRESS DAN PERFEKSIONISME DENGAN SOMATISASI PADA MAHASISWA TINGKAT AKHIR - Eka Mariska, Silvia; Fajri Sani, Suharnina; Indah Muslimah, Alfiana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
The purpose of this study was to determine the effect of Distress and Perfectionism with Somatization on final year students at the Islamic University 45 Bekasi. This study uses a quantitative method with a research design using Pearson Correlation and Multiple Linear Regression with the F Test. The subjects in this study were final year students at the Islamic University